Covid-19 Crisis and Environmental Law: Opportunities and Challenges - Nima Norouzi; Elham Ataei (Faculty of Law, Hasanuddin University, 2021)
With the outbreak of Covid-19 globally, many measures were taken to reduce this epidemic’s effects. The most important of these was the advice to stay home, which became the main line of witness slogans. With this recommendation, schools, offices, and factories were closed. The Covid-19 epidemic has had a profound effect on people’s lifestyles and is likely to have other consequences. The article’s main question is: What opportunities and challenges do the Covid epidemic pose to the environment, and how does it affect environmental rights? Quarantine policies have led to reduced production and transportation and a significant reduction in the pollution caused by these behaviors. Other effects may become apparent immediately. Covid-19 may increase survival damage in the future against contamination. Other developments may occur, including rethinking environmental and economic values and rethinking how resources are allocated and consumed, as Covid-19 affects the global, national, and local economies. Considering each of these consequences and their effects can help to develop environmental law and formulate effective strategies.